Achieving discourse truth in doing affiliated news interviews. (November 2022) - Feng, Debing
In affiliated news interviews, interviewees are both reporters and commentators, thus often caught in the dilemma of whether to interpret or report. Based on Stephen J. A. Ward's theory of pragmatic objectivity, this article responds to this question by proposing a concept of discourse truth and applying it to the analysis of affiliated news interviews collected from BBC News at Ten . It is found that journalists in such interviews tend to achieve a sense of discourse truth through three primary discourse practices, including achieving journalistic authority, emphasizing authenticity of news and displaying journalistic neutrality. These practices are in turn realized through a variety of discourse strategies such as identity credentials, personalization, modality, third-party attribution and metadiscourse expressions. The results show that objectivity can be maintained through discourse truth, even when news is interpreted. Discourse truth can reflect the authenticity of talk to some extent. It is, however, not the fact itself, but the reality constructed in the news.